2021
DOI: 10.1016/j.redox.2020.101668
|View full text |Cite
|
Sign up to set email alerts
|

Permanent cystathionine-β-Synthase gene knockdown promotes inflammation and oxidative stress in immortalized human adipose-derived mesenchymal stem cells, enhancing their adipogenic capacity

Abstract: In the present study, we aimed to investigate the impact of permanent cystathionine-β-Synthase (CBS) gene knockdown in human telomerase reverse transcriptase (hTERT) immortalized human adipose-derived mesenchymal stem cells (ASC52telo) and in their capacity to differentiate into adipocytes. CBS gene KD in ASC52telo cells led to increased cellular inflammation ( IL6, CXCL8, TNF ) and oxidative stress markers (increased intracellular reactive oxygen species and decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…In line with these findings, in immortalized human adipose-derived mesenchymal stem cells, which unlike human preadipocytes and adipocytes (current study) displayed a much higher expression of CBS than CTH gene (18), CBS gene KD promotes a cellular senescence phenotype characterized by increased inflammation and oxidative stress, and decreased H 2 S production (18). Of note, this cellular senescence phenotype resulted in adipocyte hypertrophy, when these cells differentiated into adipocytes, and attenuated their ability to differentiate into osteogenic linage (18).…”
Section: H2s In Human Adipose Tissue Adipogenesissupporting
confidence: 86%
See 1 more Smart Citation
“…In line with these findings, in immortalized human adipose-derived mesenchymal stem cells, which unlike human preadipocytes and adipocytes (current study) displayed a much higher expression of CBS than CTH gene (18), CBS gene KD promotes a cellular senescence phenotype characterized by increased inflammation and oxidative stress, and decreased H 2 S production (18). Of note, this cellular senescence phenotype resulted in adipocyte hypertrophy, when these cells differentiated into adipocytes, and attenuated their ability to differentiate into osteogenic linage (18).…”
Section: H2s In Human Adipose Tissue Adipogenesissupporting
confidence: 86%
“…Strengthening current findings, increased SIRT1 activity led to enhanced adipose tissue rejuvenation (characterized by increased cellular stemness) and decreased inflammation (12,29,43,64,78) and H 2 S administration resulted in enhanced Sirt1 expression and activity (20,51,65), preventing vascular aging (20) and cellular senescence in human fibroblasts (65). In line with these findings, in immortalized human adipose-derived mesenchymal stem cells, which unlike human preadipocytes and adipocytes (current study) displayed a much higher expression of CBS than CTH gene (18), CBS gene KD promotes a cellular senescence phenotype characterized by increased inflammation and oxidative stress, and decreased H 2 S production (18). Of note, this cellular senescence phenotype resulted in adipocyte hypertrophy, when these cells differentiated into adipocytes, and attenuated their ability to differentiate into osteogenic linage (18).…”
Section: H2s In Human Adipose Tissue Adipogenesissupporting
confidence: 84%
“…Compared with the AM_EM sample, the AM_EC sample was enriched for cell motility and inflammation-related terms according to the GO and KEGG results, and the volcano map results showed that associated gene transcription, including that of ITGA2 [ 27 ], ITGB8 [ 41 ] and CXCL8 [ 42 ], was upregulated. Since the pathogenesis of AM is closely related to the functional changes in the endometrium [ 43 ], we identified the functional changes in endometrial epithelial cells in the AM_EC and AM_EM groups and found that several identical items related to cell movement and inflammation, including positive regulation of cell migration and the IL-17 signalling pathway, appeared in the comparison of the AM_EC versus AM_EM groups in epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cysteine- β -synthase (CBS) is widely distributed in the liver, kidney, and pancreas and is the first (and rate-limiting) enzyme in the GSH synthesis pathway [ 6 , 7 ]. A recent study showed CBS gene knockdown promotes inflammation and oxidative stress in immortalized human adipose-derived mesenchymal stem cells, enhancing their adipogenic capacity [ 8 ]. In addition, the decreased expression of CBS propagates the pathogenesis of ulcerative colitis by exacerbating inflammation-induced intestinal barrier injury [ 9 ], implying an important role of CBS in mediating organ damage.…”
Section: Introductionmentioning
confidence: 99%